Terahertz magnetoplasmon-polaritons with nonlocal corrections for lossy two dimensional electron gas in GaN-based heterostructures. (24th August 2017) - Cao, Lei; Fu, Qiang; Wu, Bang; Xiong, Yongqian
Abstract: The high electron concentration in GaN-based heterostructures necessitate the consideration of nonlocal corrections in the magnetoconductivity for the study of magnetoplasmon-polaritons (MPPs) in the lossy two dimensional electron gas system with grating couplers. With the complete set of Maxwell equations, the complex dispersion frequency and absorption spectrum are calculated numerically at different magnetic field ( B max   =  10 T) and plasmon wavevectors ( k max   =  5  ×  10 7 m −1 ). Taking the AlGaN/GaN structure as a representative case, we observe the cyclotron resonance and its high order harmonics, as well as the MPP modes. The effective aspect ratio of the grating is determined according to the absorption spectrum. Effects of the nonlocal corrections on the dispersion frequency and absorption spectrum are analyzed in detail. The contributions of LO phonons, electron collisions, THz wave polarizations and retardations are also discussed.